Kinetic studies of transition metal and Ln(III) complexes of modified tetraaza-macrocyclic ligands - Ševčíková, Romana; Lubal, Přemysl, 1970-; Masarykova univerzita. Ústav chemie (2013)
Tato práce se zabývá studiem makrocyklických ligandů cyklenového a cyklamového typu. Byly studovány terodynamické, kinetické a komplexační vlastnosti těchto ligandů. Díky výjimečné termodynamické stabilitě a kinetické inertnosti mohou být tyto komplexy využity v biomedicínské nebo analytické chemii. V práci je uvedeno několik příkladů. Výsledky budou použity při konstrukci bifunčního chelátu.
This thesis deals with the study of macrocyclic ligands of cyclen and cyclam type. The thermodynamic, kinetic and complexation properties of these ligands with selected transition metal ions were studied. The exceptional thermodynamic stability and kinetic inertness of these complexes can be utilized for possible application in biomedicinal and analytical chemistry as it is demonstrated on examples given in this Thesis. The results will be used for suitable structural design of macrocyclic ligands in bifunctional chelators.
Vedoucí práce: Přemysl Lubal
Dizertace (Ph.D.)--Masarykova univerzita, Přírodovědecká fakulta, 2013
Keywords: analytická chemie; kinetika; ligandy; měď; termodynamika; tetraazamakrocykly; zinek; analytical chemistry; copper; kinetics; ligands; tetraaza-macrocyclic ligands; thermodynamics; zinc; disertace